FAKTOR-FAKTOR PENENTU PERTUMBUHAN LABA (STUDI KASUS PERUSAHAAN TERDAFTAR PADA INDEX LQ-45 BURSA EFEK INDONESIA PERIODE 2012-2016) - Fatwal Sam; Cepi Pahlevi; Erlina Pakki (Hasanuddin Journal of Applied Business and Entrepreneurship, 2018)
Companies as one form of organization in general have a specific goal to be achieved. One of the company's main objectives is to meet the interests of investors. This study aims to examine the effect of these financial ratios on profit growth, especially in companies listed on the index LQ 45 Indonesia Stock Exchange period 2012 to 2016. This research method using quantitative methods of research that emphasizes the testing of theories through the measurement of research variables with numbers and perform data analysis with statistical procedures. This study is based on the financial statements of companies listed in the LQ-45 index of the Indonesia Stock Exchange and has published financial statements in the period 2012 to 2016 that have been audited. The result of this research is Working Capital to Total Asset (WCTA) ratio has positive effect to profit growth, current ratio ratio (CR) has negative effect to profit growth. Debt to Equity Ratio (DER) has negative influence to profit growth, Turn Asset Total Asset ratio (TAT) has positive effect to profit growth, Net Profit Margin Ratio (NPM) has positive effect to profit growth, while Gross Profit Margin Ratio (GPM) to profit growth.